Atividades biológicas de extratos de fungos endofíticos - Cardoso, Mauro Guilherme Barros (2018)
Endophytic fungi are known to produce a wide variety of secondary metabolites, which play an important role in the diversification and adaptation of these microorganisms to various ecological niches. These metabolites have attracted interest from research groups and industries because of their potential for biotechnological applications such as drug development, cosmetics and food. In this context, the objective of the present work was to evaluate the presence of enzymatic activities in products of the metabolism of coffee endophytic fungi, using the snake venoms of the Bothrops moojeni and Bothrops atrox species as an enzymatic tool for the induction of phospholipase, thrombolytic and coagulant activities / anticoagulant and cytotoxic activity on human erythrocytes. Phospholipase activity was performed on agarose gel incorporated with egg yolk lecithins. Protease activity was assessed on human blood clots representing a rich source of protein substrates. Coagulation activity was assessed by counting the coagulation time of plasma citrate. Cytotoxicity on human erythrocytes was assessed with incorporation of 1% hematocrit on agarose gel. Inhibitions of 20.54%, 93.49% and 26.67% were observed on phospholipase, thrombolytic and hemolytic activities, respectively . The coagulation time was altered in the presence of only one fungus (Muscodor vitigenus HZM41), which proved to be potentiating the coagulant action. In addition, cultured fungal extracts did not show cytotoxicity on human erythrocytes under the conditions evaluated. Future studies may result in the identification of enzyme inhibitors present in fungi, with a view to their use in drug-cosmetic applications of human interest.